Cardiac tamponade caused by an ingested sewing needle - A case report - Cekirdekci, A; Ayan, E; Ilkay, E; Yildirim, H (Edizioni Minerva Medica, 2003)
Ingested sharp-pointed foreign bodies can cause serious complications. A case of a 16-year-old girl with cardiac tamponade due to ingestion of a sewing needle is presented. Ingested needles have often been reported as a cause of gastrointestinal injuries but in this rare case the sewing needle actually migrated into the myocardium.
Keywords: foreign bodies; cardiac tamponade, etiology; cardiac tamponade, surgery